Peningkatan Hasil Belajar dengan Menggunakan Media Audio Visual Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas Fase E di SMAN 1 Lengayang Pesisir Selatan - Sugiarti, Nining (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students' learning outcomes through the implementation of a technology-based learning model in two research cycles. The first cycle showed an increase in student participation, although some challenges, such as technological limitations and concept understanding, still affected the learning outcomes. In the second cycle, with improvements in teaching strategies and more effective use of learning tools, a significant enhancement in student comprehension and involvement was observed. The integration of technology-based learning with appropriate pedagogical approaches proved effective in improving student learning outcomes and promoting independent learning. These findings indicate that the integration of technology in education has a positive impact on students' cognitive development and their ability to manage their learning.